Intranasal dexmedetomidine vs. oral midazolam for premedication in children: a systematic review and meta-analysis - Zhang, Guangxuan; Xin, Li; Yin, Qingtang (Frontiers in Pediatrics, 2023)
Objective: To compare the effects of intranasal dexmedetomidine (Dex) and oral midazolam in the preoperative medication of children by using a method of Meta-analysis. Methods: Cochrane Library, Pubmed, Embase, and Web of Science were searched from inception to July 2023. Randomized controlled trials (RCTs) of intranasal Dex versus oral midazolam in pediatric premedication were collected. Stata 15.0 statistical software was used to analyze the collected data. Relative risk (RR) and 95% confidence interval (CI) were used as effect sizes. Results: A total of 11 studies with 824 children were included, containing 415 patients in the Dex group and 409 patients in the midazolam group. Compared with the oral midazolam group, the intranasal Dex group had a better preoperative sedation effect at parent-child separation (RR= 1.37, 95%CI: 1.14~1.64) and anesthesia induction (RR= 2.08, 95%CI: 1.03~4.22). In addition, there was no significant difference in the incidence of analgesia remedy (RR= 0.60, 95%CI: 0.36~1.00) the acceptance of anesthesia masks (RR= 0.97, 95%CI: 0.83~1.12), and incidence of adverse events between (RR= 0.25, 95%CI: 0.06~1.13, P= 0.072) between the intranasal Dex and oral midazolam groups. Conclusion: Compared with oral midazolam, intranasal Dex has better sedative effects of parent-child separation and anesthesia induction in pediatric premedication, but there was no difference in the incidence of anesthesia remedy, anesthesia mask acceptance, and incidence of adverse events. Therefore, compared with oral midazolam, intranasal Dex is a better choice for premedication in children.